2021
DOI: 10.1111/poms.13294
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Sex Trafficking: Data Analysis, Pattern Recognition, and Path Prediction

Abstract: Human trafficking, the exploitation of humans for monetary gain or benefit, is a widespread humanitarian issue that is typically sub‐classified into labor and sex trafficking. In the last decade, sex traffickers have used online classified advertisements to advertise sexual services. Although these advertisements are visible to the general public and law enforcement, the volume of ads, the frequency with which their posting locale changes, and the use of obfuscation tactics make it difficult for law enforcemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…It is rather well agreed that AI can help with detecting patterns (Keskin et al. 2020), supporting automatic and smart procurement (Cui et al. 2021) and achieving scientifically sound recommendations.…”
Section: Disruptive Technologies In Industry 40mentioning
confidence: 99%
See 1 more Smart Citation
“…It is rather well agreed that AI can help with detecting patterns (Keskin et al. 2020), supporting automatic and smart procurement (Cui et al. 2021) and achieving scientifically sound recommendations.…”
Section: Disruptive Technologies In Industry 40mentioning
confidence: 99%
“…2 It is reported that 10% of enterprises nowadays are using AI in their business operations (Columbus 2020a). It is rather well agreed that AI can help with detecting patterns (Keskin et al 2020), supporting automatic and smart procurement (Cui et al 2021) and achieving scientifically sound recommendations. AI and robotics are so well-developed that they outperform humans in various areas (Geva and Saar-Tsechansky 2021).…”
Section: Ai and Roboticsmentioning
confidence: 99%
“…Research related to OR and analytics efforts to reduce homelessness and the supply of sex and labor trafficking victims has only recently received attention and largely focus on three broad areas: the scope of the problem (Kosmas et al, 2020;Brelsford and Parakh, 2018), frameworks for addressing the crisis (Taylor, 2018;Kővári and Pruyt, 2014), and appropriate allocation of scarce resources to combat HT and homelessness (Chan et al, 2018;Petry et al, 2021). A second body of OR literature focuses on detection of hidden HT victims (Keskin et al, 2021;Kapoor et al, 2017;Mensikova and Mattmann, 2017), movement patterns of covert traffickers (McDonald et al, 2021;Yao et al, 2021;Amin, 2010) and long-term intervention approaches to prevent trafficking or retrafficking by increasing the efficiency and effectiveness of public services (Amadasun, 2020), as well as improving access to supportive and rehabilitative services (Azizi et al, 2018). However, little attention has been paid to using OR techniques to examine the problem of allocating scarce resources for anti-trafficking efforts, with the exceptions of Konrad (2019) and Maass et al (2020).…”
Section: Or Human Trafficking and Homelessnessmentioning
confidence: 99%
“…Mayorga et al (Mayorga et al 2019) used web scraping from an online escort service to model the movement of sex trafficking networks between different cities. Keskin et al (Keskin et al 2021) proposed a process of grouping online advertisements to predict the movement of sex trafficking networks based on where related advertisements appear. White et al (White et al 2021) used web scraping to gather data on illicit massage parlors, and determines potential contributing factors for where illicit massage parlors may be located.…”
Section: Background On or Modeling Of Sex Trafficking Networkmentioning
confidence: 99%
“…Since these networks are illicit in nature, their operations are hidden to avoid detection (Farrell & De Vries 2020, Fedina 2015, Konrad, Trapp & Maass 2017, Konrad, Trapp, Palmbach & Blom 2017. Current data for analytic approaches often comes from case files, scraped web data on sex advertisements, or data pertaining to massage parlors (Keskin et al 2021, Mayorga et al 2019, White et al 2021. This data can be viewed as the "forwardfacing" aspects of the operations of sex trafficking networks in terms of how they interact with the outside world, thus it is (somewhat) publicly accessible.…”
Section: Introductionmentioning
confidence: 99%